Incidence and Association of Seizures in Stroke Patients Undergoing Endovascular Therapies - Muhammad Hamza Khan Alizai, Samiyah Tasleem, Husnain Hashim, Kamran Afzal, Muhammad Tahir, Sana Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endovascular therapies have revolutionized the treatment of stroke, but post-stroke seizures continued as significant complication that impacted morbidity. Objectives: We examined the incidence and association of seizures in stroke patients undergoing endovascular therapy (EVT). Methods: Investigation included 384 hospitalized patients with acute ischemic or hemorrhagic stroke undergoing EVT. To distinguish and investigate the stroke, and to identify subtypes of stroke using the TOAST classification, the incidence of seizures was determined in stroke patients following EVT through brain imaging. Results: We analyzed the demographic and clinical characteristics of 384 stroke patients who underwent EVT and had seizures. Seizures were found to occur in 6.51% of EVT patients (p>0.05). Occurrence of seizures was non-substantially affected by comorbidities like hypertension, cardiac maladies and diabetes. Majority of stroke patients (82.81%) suffered from ischemic strokes, while only 17.18% had hemorrhagic strokes. Large artery atherosclerosis was the most prevalent subtype of stroke associated with seizures following EVT. The severity of the stroke and existing of cortical involvement were not significantly associated with seizures (p<0.05), whereas lower age and early seizures after EVT were associated with a marginally increased risk of experiencing seizures. Overall, study indicated that incidence of seizures following EVT was relatively low and influenced by particular factors. Practical implication: This study emphasized the need for personalized patient care strategies, including vigilant surveillance for seizures and preventative interventions, to enhance the outcomes of stroke patients undergoing endovascular therapy. Conclusion: Seizures are a significant complication of EVT for stroke patients. Stroke severity and etiology may influence seizure risk, highlighting the significance of vigilant monitoring and proactive management to reduce the incidence of seizures in this patient population. Keywords: Endovascular treatment; Epidemiology; Epilepsy; Hemorrhage; Seizures; Thrombectomy.